Epidemiological Differences of Chronic Viral Hepatitis C in Caucasian and Asian Races Taking into Account Population Interferon Gene Polymorphism - S. I. Malov; I. V. Malov; E. D. Savilov; D. . Gantulga; I. A. Miroshnichenko; L. A. Stepanenko; O. B. Ogarkov; N. . Erdenebayar; L. S. Orlova; N. . Bira; I. V. Ushakov (Эпидемиология и вакцинопрофилактика)
Aim of study: to give a comparative epidemiological characteristic of hepatitis C in Mongolia and Irkutsk region taking into account races, INF λ3 gene polymorphism and INF λ4 gene polymorphismin studied population. Epidemiological evidence of hepatitis C in Mongolia, in contrast to the Irkutsk region, characterized higher prevalence, domination of seropositive persons in age older than 50 years, domination in the circulation of the 1st virus genotype. In the population of Mongolia was revealed high frequency some nucleotide INF λ3 and INF λ4 gene polymorphism. These genetic markers are more favorable for natural history of hepatitis C. It explains the high rate of spontaneous hepatitis C virus clearance among people of Asian race.